KEPUASAN MEREK MEMEDIASI PENGARUH SENSORIK MEREK TERHADAP LOYALITAS MEREK TELEPON PINTAR APPLE: KEPUASAN MEREK MEMEDIASI PENGARUH SENSORIK MEREK TERHADAP LOYALITAS MEREK TELEPON PINTAR APPLE - Siti Barokah; Oryz Agnu Dian Wulandari; Anisa Nur Andina (Universitas Putera Batam, 2019)
The amount of interest in the use of smartphones has created intense competition among smartphone vendors. Companies are required not only to create customer satisfaction but also to find and build a management system that is professionally able to retain customers. This research is a quantitative study using online survey methods. The samples in this study were all Apple brand smartphone users. the variables used are Brand Sensory, Brand Satisfaction, and Brand Loyalty. Sampling with purposive sampling. Data analysis uses structural equation modeling (SEM) to test models and hypotheses. The analysis shows that brand sensory has a positive effect on brand satisfaction and brand loyalty. Brand Satisfaction has a positive effect on Brand Loyalty. Brand satisfaction mediates the sensory influence of brands on brand loyalty.